2013
DOI: 10.1016/j.antiviral.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of feline coronaviruses with peptidyl compounds targeting coronavirus 3C-like protease

Abstract: Feline coronavirus infection is common among domestic and exotic felid species and usually associated with mild or asymptomatic enteritis; however, feline infectious peritonitis (FIP) is a fatal disease of cats that is caused by systemic infection with a feline infectious peritonitis virus (FIPV), a variant of feline enteric coronavirus (FECV). Currently, there is no specific treatment approved for FIP despite the importance of FIP as the leading infectious cause of death in young cats. During the replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 44 publications
3
62
0
1
Order By: Relevance
“…The PEC levels in absence of bile acid and MNV-1 levels in cyclohexamide-treated cells indicate the levels of internalized viruses (Figure 1A, 1B). As reported previously, CA074-Me significantly reduced the replication of feline coronavirus 1146 strain in CRFK cells (Kim et al, 2013; Regan et al, 2008) (data not shown).…”
Section: Resultssupporting
confidence: 88%
“…The PEC levels in absence of bile acid and MNV-1 levels in cyclohexamide-treated cells indicate the levels of internalized viruses (Figure 1A, 1B). As reported previously, CA074-Me significantly reduced the replication of feline coronavirus 1146 strain in CRFK cells (Kim et al, 2013; Regan et al, 2008) (data not shown).…”
Section: Resultssupporting
confidence: 88%
“…The https://doi.org/10.1016/j.vetmic.2019.108398 Received 10 July 2019; Received in revised form 21 August 2019; Accepted 21 August 2019 released viral proteins form the replicase-transcriptase complex, which is required for RNA replication and transcription of the subgenomic RNAs, thus inhibition of viral proteases blocks viral replication. We have previously reported the synthesis of protease inhibitors for feline coronavirus (Kim et al, 2012a(Kim et al, , 2013Kim et al, 2015), and showed the efficacy of one of the inhibitors, GC376, in cats with experimentally induced FIP (Kim et al, 2016) and naturally-occurring FIP in a field trial (Pedersen et al, 2018). We have also reported the amino acid changes (N25S, A252S and K260 N) in the 3CLpro of feline coronavirus collected from a patient who was treated with GC376 but did not show clinical resistance to multiple rounds of treatment in the field trial (Pedersen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the substrate-binding channel of the 3CLSP or 3CL protease is a large cavity, supplementary studies may need to more accurately characterize the compound-binding sites to design and optimize inhibitors. For Norwalk virus and feline coronavirus, the transition state 3C-like protease inhibitors were designed and synthesized, and exhibited notable inhibitory effects against viral replication (Tiew et al, 2011;Kim et al, 2013). Therefore, transition state compounds that will optimally generate hydrophobic interactions and hydrogen bonds with the side chain amino acid residues are needed, and animal studies should also be conducted to develop antiviral drugs against PRRSV and PEDV in the future.…”
Section: Discussionmentioning
confidence: 99%
“…During replication, the PL1pro and PL2pro proteases cleave the N-proximal region of pp1a/pp1ab, and the 3CLSP/3CL protease cleaves the viral polyprotein at other conserved inter-domain junctions (Tian et al, 2009;Ye et al, 2016). The viral 3CLSP/3CL proteases play an essential role in artertivirus and coronavirus replication; therefore, they have received much attention as potential key antiviral targets (including TGEV, FIPV, IBV and SARS-CoV) (Anand et al, 2002;Kim et al, 2013;Lee et al, 2007;Xue et al, 2008).…”
mentioning
confidence: 99%